SCHOOL CLOSURE DURING PANDEMIC; WHAT HAS BEEN MISSING? - Maria - Melinia; Dedi - Irawan; M. Iqbal - Ripo Putra; Dayat - Dayat (IKIP PGRI Pontianak, 2023)
Abstract This descriptive study aims to determine the occurrence of learning losses in addition to learning aspects such as knowledge, skills, and attitudes of students from learning during the pandemic period taken from SMPN 05 Toba and SMAN 1 Toba. This study used descriptive qualitative method. This study involved 4 students and 4 teachers from 1 school. This study uses semi-structured interviews and interview guides as data collection tools. Data collection using interview guides related to learning during the pandemic.The results showed that it was true that there was a learning loss. This learning loss has occurred since the pandemic period where schools closed and made all schools have to do learning from home, so students are required to learn independently from their respective homes while in reality a learning process really needs interaction between students and teachers. The influence of learning loss occurs in the cognitive aspect, namely knowledge and skills and also in the non-cognitive aspect, namely attitude, where the pandemic period currently faced by schools is experiencing learning loss in students.